Light-Emitting Polymer Nanocomposites - Kyle Gipson; Brett Ellerbrock; Kathryn Stevens; Phil Brown; John Ballato (Journal of Nanotechnology)
Inorganic nanoparticles doped with optically active rare-earth ions and coated with organic ligands were synthesized in order to create fluorescent polymethyl methacrylate (PMMA) nanocomposites. Two different aromatic ligands (acetylsalicylic acid, ASA and 2-picolinic acid, PA) were utilized in order to functionalize the surface of Tb3+ : LaF3 nanocrystals. The selected aromatic ligand systems were characterized using infrared spectroscopy, thermal analysis, rheological measurements, and optical spectroscopy. Nanoparticles produced in situ with the PMMA contained on average 10 wt% loading of Tb3+ : LaF3 at a 6 : 1 La : Tb molar ratio and ~7 wt% loading of 4 : 1 La : Tb molar ratio for the PA and ASA systems, respectively. Measured diameters ranged from 457±176 nm to 150±105 nm which is indicative that agglomerates formed during the synthesis process. Both nanocomposites exhibited the characteristic Tb3+ emission peaks upon direct ion excitation (350 nm) and ligand excitation (PA : 265 nm and ASA : 275 nm).